Pengembangan Daging Analog Berbumbu: Proporsi Daging Analog-Bumbu Rendang dengan Komposit Coconut Powder-Fiber Cream Ditinjau dari Preferensi Konsumen - Regina, Celline Nikita; Sutiadiningsih, Any; Romadhoni, Ita Fatkhur; Restami, Mafisa (Indo-MathEdu Intellectuals Journal, 2026)
The increasing public interest in plant-based foods has encouraged the development of alternative products, one of which is analog meat with rendang seasoning. This study aims to analyze the effect of variations in the proportion of analog meat and rendang seasoning on consumer preference based on color, aroma, and taste attributes, and to determine the best formulation. The study used an experimental method with a quantitative approach. Several formulations with varying proportions of analog meat and rendang seasoning were tested using a hedonic test on 40 untrained panelists who were selected purposively with the criteria of liking rendang products. Data were analyzed using descriptive percentage analysis, Friedman test, One Way Analysis of Variance (ANOVA), and Duncan's advanced test. The best formulation was then analyzed using a proximate test. The results showed that variations in the proportion of analog meat and rendang seasoning significantly influenced the panelists' preference levels for color, aroma, and taste attributes (p<0.05). The formulation with a proportion of analog meat and rendang seasoning of 61.5%:38.5% was the most preferred formulation. Proximate analysis showed that the formulation contained 16.80 g of protein per 100 g, with an energy content of 243.20 kcal, fat 12.00 g, carbohydrate 17.00 g, water content 52.00 g, and ash content 2.20 g. These results indicate that the selected formulation has good sensory characteristics and nutritional content that supports the development of analog meat as a plant-based food alternative